Evaluation of prognostic value of lung ultrasound in st-segment elevation myocardial infarction killip i. (2nd May 2022) - Carreras, J; Simon-Ramon, C; Vidal-Burdeus, M; Rodriguez-Sotelo, L; Giralt-Borrell, T; Izquierdo-Marquisa, A; Rivas-Lasarte, M; Llao-Ferrando, JI; Ariza-Sole, A; Sionis, A; Ribas-Barquet, N; Vaquerizo-Montilla, B
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Societat Catalana de Cardiologia (SCC) Sociedad Española de Cardiología (SEC) Introduction: About 80-90% of patients admitted for ST-segment elevation myocardial infarction (STEMI) present with no signs of heart failure at admission. Heart failure at admission is one of the most relevant prognostic factors in STEMI, whereas incidence and prognostic significance of HF developed during hospitalization is unclear. B-lines in lung ultrasound (LUS) provide useful diagnostic and prognostic information in heart failure patients with the potential to stratify the risk of complications in patients presenting with STEMI KKI. Purpose: To assess the capacity of the lung ultrasound to predict heart failure developing or death during hospitalization in patients admitted for STEMI KKI Methods: This is a prospective observational multicenter study. Consecutive patients admitted for STEMI KKI in four tertiary hospitals were included, exclusion criteria were patients with cardiac arrest at presentation, severe lung disease or hemodialysis. The LUS was carried out by an independent operator blinded to clinical data in the first 24 hours after admission. We counted B-lines using 8-scan site LUS protocol and divided patients in two groups : wet lung group (3 or more B-lines in at least one zone) and dry lung (no positive zone). The primary endpoint was a composite of clinical congestive heart failure, cardiogenic shock, or mortality during the index hospitalization. Results: From June 2020 to November 2021, 221 patients STEMI KKI patients were included. Fifty-four patients (25, 4%) had a wet lung according to the LUS. Seventeen patients (7, 7%) presented the primary outcome (all of them developed congestive heart failure, 1 of them cardiogenic shock and 2 of them died during hospitalization). Fourteen in 54 wet-lung patients (25, 9%) presented the primary outcome whereas only 3 in 167 (1, 7%) of the dry-lung patients [relative risk of 14, 4 (IC 95% 4, 3-48, 3)]. Patients who develop the primary outcome had no differences in NTproBNP at admission but had higher NTproBNP peak, higher troponin T peak, lower left ventricular ejection fraction and longer length of stay. Conclusions: In patients admitted with STEMI KKI, presenting 3 or more B-lines at least at one lung zone in the LUS at first 24 hours after admission was strongly associated with worse prognosis during hospitalization. LUS allows a better risk classification of patients and may potentially discriminate those with potential risk of complications during hospitalization from those with an excellent prognosis who can benefit from early discharge.